2007
DOI: 10.1007/s11461-007-0051-y
|View full text |Cite
|
Sign up to set email alerts
|

Change of trunk sap flow of Ginkgo biloba L. and its response to inhibiting transpiration treatment

Abstract: For this paper, GREENSPAN sap flow system was used to monitor the dynamics of trunk sap flow of Gingkgo biloba. Results indicate that sap flow velocity is significantly different among different heights, depths, and directions of the trunk. Sap flow velocity at the upper position of the trunk is higher than that of the middle and lower position, but cumulative flux is not significantly different among the upper, middle and lower sections. Sap flow velocity at 10 mm reached the most and that at 20 mm the least.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Some error may have been introduced by taking measurements of trees and hedges at different heights, however, it is likely to have affected sap flux density rather than sap flow. Shoujia et al (2007) observed that height of sensor installation along the trunk significantly affected sap flux density, but not cumulative sap flux in Gingko biloba.…”
Section: Sap Flow and Wood Anatomymentioning
confidence: 91%
“…Some error may have been introduced by taking measurements of trees and hedges at different heights, however, it is likely to have affected sap flux density rather than sap flow. Shoujia et al (2007) observed that height of sensor installation along the trunk significantly affected sap flux density, but not cumulative sap flux in Gingko biloba.…”
Section: Sap Flow and Wood Anatomymentioning
confidence: 91%